Simulation Oriented Layer of Embedded Software Architecture for Rapid Development of Custom Embedded Systems Virtual Simulators Used in Didactics - Andrzej Radecki; Tomasz Rybicki (Applied Sciences, 2022)
The application of the proposed Simulation Oriented Layer in the embedded-software architecture is shown in this paper. The SOL’s purpose is to deliver only limited and highly desirable microprocessor-system functionality to the Application Layer, which would be implemented in a virtual simulator without requiring its complex development. It was used in two virtual simulators of embedded systems, as presented in the article. Each virtual simulator covers one customized embedded system (RPILAB and TMSLAB) used for didactical purposes. On each embedded platform, a different method of system-functionality simulation was shown. Presented virtual simulators can run recompiled (for the virtual-simulator platform) programs in a seamless process, giving real-like experiences for programmers, who can verify and test their high-level solutions. Being accurately chosen, taken for the simulation because of essential and limited functionality, and used in the Application Layer allowed for the rapid design of the virtual simulators. Unit- and functional-test results using RPILAB- and TMSLAB-embedded systems and their virtual simulators are shown in this paper. Both simulators of real RPILAB and TMSLAB platforms are used with success in the didactical process, at the Institute of Automatic Control in Lodz University of Technology, since the COVID-19 pandemic.